Arctigenin Attenuates Learning and Memory Deficits through PI3k/Akt/GSK-3β Pathway Reducing Tau Hyperphosphorylation in Aβ-Induced AD Mice - Qi, Yue; Dou, De-Qiang; Jiang, Hong; Zhang, Bing-Bing; Qin, Wen-Yan; Kang, Kai; Zhang, Na; Jia, Dong (Planta Medica, 2017)
Arctigenin is a phenylpropanoid dibenzylbutyrolactone lignan compound possessing antitumor, anti-inflammatory, anti-influenza, antioxidant, antibacterial, and hypoglycaemic activities. Our previous study demonstrated that arctigenin exerts neuroprotective effects both in vitro and in vivo in a Parkinsonʼs disease model. However, the exact mechanism through which arctigenin improves amyloid beta-induced memory impairment by inhibiting the production of the hyperphosphorylated tau protein is unknown. Amyloid β1–42 was slowly administered via the intracerebroventricular route in a volume of 3 µL (≈ 410 pmmol/mouse) to mice. The mice were administered arctigenin (10, 40, or 150 mg/kg) or vehicle starting from the second day after amyloid β1–42 injection to the end of the experiment. Behavioural tests were performed from days 9 to 15. On day 16 after the intracerebroventricular administration of amyloid β1–42, the mice were sacrificed for biochemical analysis. Arctigenin (10–150 mg/kg) significantly attenuated the impairment of spontaneous alternation behaviours in the Y-maze task, decreased the escape latency in the Morris water maze test, and increased the swimming times and swimming distances to the platform located in the probe test. Arctigenin attenuated the level of phosphorylated tau at the Thr-181, Thr-231, and Ser-404 sites in the hippocampus, and increased the phosphorylation levels of phosphatidylinositol-3-kinase, threonine/serine protein kinase B, and glycogen synthase kinase-3β. Arctigenin effectively provides protection against learning and memory deficits and in inhibits hyperphosphorylated tau protein expression in the hippocampus. The possible mechanism may occur via the phosphatidylinositol-3-kinase/protein kinase B-dependent glycogen synthase kinase-3β signalling pathway.
Keywords: Alzheimerʼs disease tau; glycogen synthase kinase-3β; phosphatidylinositol-3-kinase; threonineserine protein kinase B